A mixed methods sequential explanatory study of the psychosocial factors that impact on midwives' confidence to provide bereavement support to parents who have experienced a perinatal loss. (September 2018) - Agwu Kalu, Felicity; Coughlan, Barbara; Larkin, Philip
Highlights: The provision of effective bereavement support to grieving parents is challenging for many midwives because of inadequate level of confidence. The psychosocial factors that impact on midwives' confidence are midwives' awareness of the needs of bereaved parents, their own inner strength and the organizational support they received at their place of work. Midwives need adequate education and training as well as emotional and practical support from their organizations to develop their confidence to provide effective care to bereaved parents. Abstract: Background: Perinatal bereavement is traumatic for many parents. Not only is the experience itself emotionally painful, the impact on their lives is made more difficult if midwives are unable to provide appropriate care to the parents. Aim of the study: To explore within an Irish context, the psychosocial factors that impact on midwives' confidence to provide bereavement support to parents who have experienced a perinatal loss. Design: A mixed methods sequential explanatory design was used to complete this two-phased study from August 2013 to July 2014. Ethical approval was granted from Ethics Committees of three maternity hospitals and a University in Ireland. The recruitment process for the survey occurred in August 2013 and July 2014 for the focus groups. Methods: A series of univariate and multivariate analysis were used to analyze the quantitative data using IBM Statistical Package for the Social Sciences (SPSS; version 20). The qualitative data were analyzed using qualitative content analysis. Steps were taken to ensure data validity and reliability. Results: The overall meta-inference of this study is that the majority of the midwives did not have adequate levels of confidence to provide bereavement support to grieving parents. The psychosocial factors that impact on midwives' confidence were identified as the midwives' awareness of the needs of bereaved parents, their own inner strength and the organizational support they received at their place of work. Conclusion: Improving midwives' bereavement support knowledge and skills is essential for promoting their confidence. Midwives also need adequate emotional and practical support from their organizations.